2007
DOI: 10.1124/dmd.106.010801
|View full text |Cite
|
Sign up to set email alerts
|

Role of P-glycoprotein in the Intestinal Absorption of Glabridin, an Active Flavonoid from the Root ofGlycyrrhiza glabra

Abstract: ABSTRACT:Glabridin is a major constituent of the root of Glycyrrhiza glabra, which is commonly used in the treatment of cardiovascular and central nervous system diseases. This study aimed to investigate the role of P-glycoprotein (PgP/MDR1) in the intestinal absorption of glabridin. The systemic bioavailability of glabridin was approximately 7.5% in rats, but increased when combined with verapamil. In single-pass perfused rat ileum with mesenteric vein cannulation, the permeability coefficient of glabridin ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
4
56
1
Order By: Relevance
“…14,25) The uptake of quinine, a drug for malaria and excreted by P-gp, into the brain was increased by verapamil. 26) These reports suggest that verapamil inhibited P-gp both in the small intestine and in the livers of mice, resulting in an increased amount of kaempferol, which in turn enhanced the suppressive effect on AhR transformation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…14,25) The uptake of quinine, a drug for malaria and excreted by P-gp, into the brain was increased by verapamil. 26) These reports suggest that verapamil inhibited P-gp both in the small intestine and in the livers of mice, resulting in an increased amount of kaempferol, which in turn enhanced the suppressive effect on AhR transformation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Many flavonoids are substrates of the most pharmacologically relevant ABC transporters, P glycoprotein/ MDR1, MRP, and BCRP [123] [124] but so far scientific effort has focused on the modulation of the transporter by flavonoids [125]. Whereas some flavonoids were shown to inhibit MDR1-mediated transport processes by directly interacting with the vicinal ATP-and steroid-binding sites [126], others (like (-) epicatechin from green tea) were shown to activate MDR1 by a heterotropic allosteric mechanism [127].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In the present study, both standard chemical glabridin and LFO glabridin are one-order of magnitude lower in AUC value than quercetin, but glabridin existed in the blood as the aglycone form. In a recent study (34), the authors reported that glabridin was mainly metabolized by glucuronidation and the metabolic capacity of intestine microsomes was 1/15 to 1/20 of that in liver microsomes. The information also means that dietary * Mean values of plasma glabridin profiles in each group were analyzed using non-compartmental model.…”
Section: Discussionmentioning
confidence: 99%